STUDY OF ELECTROOPTICS BEHAVIOUR OF NAPHTHALENE AND ANTHRACENE - Firdausi, K Sofjan; Khumaeni, Ali; Richardina, Very; Arianto, Fajar; Budi, Wahyu Setia (BERKALA FISIKA, 2015)
In this paper, we demonstrate electro-optics behaviour of naphthalene and anthracene using change of polarization of sample induced by external electric field. The source of light for polarization was 1 mW-he-ne Laser 633 nm. The induced external Electric field was produced by high DC voltage 0 â€“ 7 kV. The samples were diluted in solutions-form using wash-benzene. The result shows that anthracene has higher polarizability than naphthalene, which is indicated by higher change of polarization in anthracene than naphthalene. The Assumption that potential difference is proportional to the distance between molecules is shown qualitatively by graphs of Van der Waals potential energy or force between molecules. In this case, anthracene has higher level Energy than naphthalene so that it can be used in visible excitation for environmental spectroscopy. Keywords: electro-optics, polarization, naphthalene, anthracene, Van der Waals potential energyÂ